Description of a new species of Neoparaphytoseius Chant and McMurtry (Acari: Mesostigmata: Phytoseiidae) from Peru, with a redefinition of the genus - Jiménez, Sofía; Mcmurtry, James A.; de Moraes, Gilberto J. (Zootaxa, 2014)
Neoparaphytoseius charapa n. sp. is described, based on the morphology of adult females and males collected on Inga edulis (Mart.) (Fabaceae) in northeastern Peru. Neoparaphytoseius Chant & McMurtry is redefined on the basis of the new species and re-examination of its type species N. sooretamus Chant & McMurtry.